PENINGKATAN HASIL BELAJAR MUATAN PELAJARAN IPA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS V SD N BAWANG 02 TAHUN PELAJARAN 2020/2021 - Nofiana Ulfa; Mei Fita Asri Untari; Ulin Nafi’ah (Universitas Negeri Medan, 2021)
Abstrak : This study aims to determine the increase in learning outcomes in science content for fifth grade students of SD N Bawang 02. The subjects of this study were fifth grade students with 20 students consisting of 6 male students and 14 female students. The method used in this research is observation, documentation, and tests. This type of research is classroom action research which is carried out in three cycles where each cycle contains two lessons. The use of learning models and media that are less varied in online learning causes low learning outcomes for science content as seen from the average grade V SD N Bawang 02, that is, out of 20 students only 5 students can achieve the KKM, the results of the daily test of the science content of students with 25% completeness percentage. As for the KKM for the fifth grade science subject at SD N Bawang 02, it is 75. The results show that the discovery learning model can improve the science learning outcomes of the fifth grade students of SD N Bawang 02 for the 2020/2021 academic year. This can be seen through the improvement of learning outcomes from Cycle I to Cycle III. An increase in students who complete learning from Cycle I learning 1 to Cycle I learning 2 10%, an increase in Cycle I learning 2 to Cycle II learning 1 15%, an increase in Cycle II learning 1 to Cycle II learning 2 15%, an increase in Cycle II learning 2 to Cycle III learning 1 5%, and an increase in Cycle III learning 1 to Cycle III learning 2 30%. Keywords: Science Learning Outcomes, Discovery Learning Model Abstrak :Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar muatan pelajaran IPA siswa kelas V SD N Bawang 02. Subyek penelitian ini adalah siswa kelas V dengan jumlah siswa 20 orang yang terdiri dari 6 siswa laki-laki dan 14 siswa perempuan. Metode yang digunakan dalam penelitian ini adalah observasi, dokumentasi, dan tes. Jenis penelitian ini adalah penelitian tindakan kelas yang dilaksanaksan dalam tiga siklus dimana tiap sikluasnya terdapat dua pembelajaran. Penggunaan model dan media pembelajaran yang kurang variatif dalam pembelajaran daring menyebabkan rendahnya hasil belajar muatan pelajaran IPA dilihat dari rata-rata nilai kelas V SD N Bawang 02 yaitu dari 20 siswa hanya 5 siswa yang dapat mencapai KKM, hasil ulangan harian muatan pelajaran IPA siswa dengan presentase ketuntasan 25%. Sedangkan untuk KKM mata pelajaran IPA kelas V SD N Bawang 02 yaitu 75. Hasil penelitian menunjukkan bahwa model pembelajaran discovery learning dapat meningkatkan hasil belajar IPA siswa kelas V SD N Bawang 02 tahun pelajaran 2020/2021. Hal ini dapat diketahui melalui peningkatan hasil belajar dari Siklus I sampai Siklus III. Peningkatan siswa yang tuntas belajar dari Siklus I pembelajaran 1 ke Siklus I pembelajaran 2 10%, peningkatan Siklus I pembelajaran 2 ke Siklus II pembelajaran 1 15%, peningkatan Siklus II pembelajaran 1 ke Siklus II pembelajaran 2 15%, peningkatan Siklus II pembelajaran 2 ke Siklus III pembelajaran 1 5%, dan peningkatan Siklus III pembelajaran 1 ke Siklus III pembelajaran 2 30%. Kata Kunci : Hasil Belajar IPA, Model Pembelajaran Discovery Learning